Numerical simulation and validation of ocean waves measured by an Along-Track Interferometric Synthetic Aperture Radar - 张彪 何宜军 Paris W. VACHON (Chinese journal of oceanology and limnology, 2008)
A new nonlinear integral transform of ocean wave spectra into Along-Track Interferometric Synthetic Aperture Radar （ATI-SAR） image spectra is described. ATI-SAR phase image spectra are calculated for various sea states and radar configurations based on the nonlinear integral transform. The numerical simulations show that the slant range to velocity ratio （R/V）, significant wave height to ocean wavelength ratio （Hi2）, the baseline （2B） and incident angle （0） affect ATI-SAR imaging. The ATI-SAR imaging theory is validated by means of Two X-band, HH-polarized ATI-SAR phase images of ocean waves and eight C-band, HH-polarized ATI-SAR phase image spectra of ocean waves. It is shown that ATI-SAR phase image spectra are in agreement with those calculated by forward mapping in situ directional wave spectra collected simultaneously with available ATI-SAR observations. ATI-SAR spectral correlation coefficients between observed and simulated are greater than 0.6 and are not sensitive to the degree of nonlinearity. However, the ATI-SARoPhase image spectral turns towards the range direction, even if the real ocean wave direction is 30. It is also shown that the ATI-SAR imaging mechanism is significantly affected by the degree of velocity bunching nonlinearity, especially for high values of R/V and H/2.